10 year follow up after first stroke: Mortality rate and health-related quality of life - Aðalbjörg Birgisdóttir 1993- (2019)
Introduction: This thesis is part of the larger project exploring 10-year health-related outcome amongst stroke survivors. Objective: (1) Report one-, five- and 10-year mortality after first stroke. (2) Describe health-related quality of life (HRQoL) and (3) report self-rated health amongst survivors 10 years after first stroke. Design: A cross-sectional descriptive study. Method: Sample was identified through SAGA medical records in accordance with the following inclusion criteria: Living in Iceland at the time of stroke, over 18 years and diagnosed with first stroke from 01/10/2007-30/09/2008. Mortality was determined through medical records. The International Spinal cord injury quality of life basic data set (ISCIQoL) questionnaire was used to measure HRQoL. Participants were then asked to rate their health from bad-excellent. Result: 240 cases met the inclusion criteria, 95 survived and 145 were deceased. One-year mortality rate was 23.8%, Five-year mortality rate was 39.2% and 10-year mortality rate was 60.4%. The mean age of death was consistent through all follow ups. All domains of ISCIQoL, life as a whole, physical and psychological had the median 8/10. Individuals 85-years and older were less satisfied with their life as a whole (P=0,032). Majority of sample rated their health reasonable, good or very good. A strong positive correlation was found between all domains of HRQoL and between HRQoL and Self-rated health (p<.001). Conclusion: Mortality among stroke sufferers in Iceland at one-year is similar to other countries, but the five-year and the 10-year mortality rates are a bit lower than most previous studies report. From this study it can be hypothesized that HRQoL amongst Icelandic stroke survivors 10 years after first stroke is good and their self-rated health is positive. However, older adults are likely to rate themselves lower in both. Inngangur: Þessi ritgerð er byggð á stærri rannsókn sem skoðar afdrif einstaklinga tíu árum eftir fyrsta heilaslag. Markmið ritgerðarinnar eru: (1) gera ...